A Profile of Fatal Head Injury in Homicidal Deaths (A Retrospective Study of 5 Years) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Jamnagar region, Gujarat state, enjoys a relatively low incidence of homicide in India. A retro- spective review of 179 cases of homicidal death brought during the years 2000 to 2004 was conducted. Out of these 179 cases of homicide there were 64 cases of fatal head injuries with 48 male and 15 female victims. There was one case of newborn whose sex could not be deter- mined as the part brought for post mortem examination was only the head. The ratio of male to female victims was 3.2:1. Weapon of choice was a hard, blunt and heavy object. Just over 40.63% of all cases in the region occurred in the age groups from 21- 40 years of age. Even in fatal head injury homicides, incidence of skull bone fracture was quite low. Minimum survival duration of the victim was seen in majority of the cases.
Keywords: Homicide; Head Injury; Blunt Force; Jamnagar